Transformasi manajemen pendidikan islam melalui kepemimpinan pendiri pesantren non-genealogis: studi multi-kasus pada KH. Ainul Yaqin Jogoroto dan KH. Abdul Hanan Maksum Kwagean - Faizin, M Faiq; Supriyatno, Triyo; Susilawati, Samsul (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3600, 2025)
This study aims to explore how the founding leadership of non-lineage kiai contributes to the transformation of Islamic education management within pesantren institutions. The research focuses on two pioneering figures: KH. Ainul Yaqin, founder of Pondok Pesantren Hamalatul Qur’an in Jogoroto Jombang, and KH. Abdul Hanan Maksum, founder of Pondok Pesantren Fathul Ulum in Kwagean Kepung Kediri. Both represent a distinctive phenomenon in the pesantren tradition, as non-hereditary kiai who successfully established Islamic educational institutions from the ground up through an integration of managerial, spiritual, and cultural approaches. This research employs a qualitative multi-case study method, using participatory observation, in-depth interviews, and document analysis as the main data collection instruments. Data were analyzed interactively through the stages of reduction, presentation, and conclusion drawing. The findings reveal that the founding leadership of non-lineage kiai plays a vital role in formulating institutional visions, building teacher and student regeneration systems, and developing adaptive management patterns that respond to contemporary challenges while maintaining pesantren traditions. Both pesantren have evolved through transformative leadership strategies that integrate spirituality, professionalism, and innovation in Islamic education. This study concludes that the model of founding leadership among non-lineage kiai offers an alternative paradigm for modern pesantren management, particularly in strengthening human resource development and institutional independence.